TAVI and Post Procedural Cardiac Conduction Abnormalities - Mangieri, Antonio; Montalto, Claudio; Pagnesi, Matteo; Lanzillo, Giuseppe; Demir, Ozan; Testa, Luca; Colombo, Antonio; Latib, Azeem (Frontiers in Cardiovascular Medicine, 2018)
Transcatheter aortic valve implantation (TAVI) is a worldwide accepted alternative for treating patients at intermediate or high risk for surgery. In recent years, the rate of complications has markedly decreased except for new-onset atrioventricular and intraventricular conduction block that remains the most common complication after TAVI. Although procedural, clinical, and electrocardiographic predisposing factors have been identified as predictors of conduction disturbances, new strategies are needed to avoid such complications, particularly in the current TAVI era that is moving quickly toward the percutaneous treatment of low-risk patients. In this article, we will review the incidence, predictive factors, and clinical implications of conduction disturbances after TAVI.